Gênese e Classificação da Coquina de Camaquã, Formação Corumbataí (Neopermiano), na Região de Rio Claro, SP - Simões, Marcello Guimarães [UNESP]; Torello, Fernanda de Freitas [UNESP]; Rocha-Campos, Antonio Carlos (My University, 1996)
Analysis of the taphonomic signatures of a well preserved, silicifled coquina (Pinzonella neotropica assemblage) from the Camaquã outcrop, upper part of the Corumbataí Formation (Late Permian), in the Rio Claro region, state of Sáo Paulo, allowed interpretation of processes involved in its origin as related to high energy events (storms). The coquina occurs as a lenticular body, 2-11 cm thick and extending laterally for about 120 m. Basal contact of the coquina is sharp and erosive. Its upper contact is sharp. The concentration is dominated by pelecypods including the shallow burrowers (Pinzonella neotropica, Jacquesia brasiliensis), intermediate burrower (Pyramus anceps) and semi-infaunal forms (Naiadopsis lamellosus). All these species are suspension feeders. Besides sand-sized or even smaller shell fragments, there occur disarticulated, complete shells which are commonly abraded but do not show any signs of bioerosion or incrustation. In vertical side view, the shells are mainly convex-up, nested or stacked, while in plan-view they show random orientation. Multiple discontinuous grading is visible. These taphonomic signatures suggest that the origin of the skeletal accumulation is related to high energy events (possibly storm flows) in a proximal environment. The amalgamated nature of the Camaquã coquina records several episodes of erosion and deposition.